2013
DOI: 10.1007/s10792-013-9731-9
|View full text |Cite
|
Sign up to set email alerts
|

Internal drainage for chronic macula-involving serous retinal detachment in idiopathic central serous chorioretinopathy

Abstract: Conventional treatment of idiopathic central serous chorioretinopathy (ICSC) consists of argon laser, photodynamic therapy, or observation. However, in cases of atypical bullous ICSC with exudative detachment preventing any laser therapy, a surgical approach with external drainage of fluid has been performed. We present a case of ICSC with persistent macula involving exudative retinal detachment without evidence of uveitis that responded favorably to internal drainage by vitrectomy along with a scleral buckle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…He obtained a complete SRF resolution the day after surgery and a BCVA of 20/80 with no recurrence at six-months of follow-up [ 14 ]. Even if the external drainage techniques avoid the risks related to intraocular surgery, carry the threat of subretinal or choroidal hemorrhages [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…He obtained a complete SRF resolution the day after surgery and a BCVA of 20/80 with no recurrence at six-months of follow-up [ 14 ]. Even if the external drainage techniques avoid the risks related to intraocular surgery, carry the threat of subretinal or choroidal hemorrhages [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…About internal drainage techniques (pars plana vitrectomy, scleral buckling with cryopexy and retinotomy) have been successfully employed in RD associated to uveitis and may ensure to remove all subretinal fluid [ 27 , 38 , 39 , 40 ]. Nevertheless, these treatments often have been reported as a result of misdiagnosed bCSCR [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cases also indicated that transpupillary thermotherapy seemed to be effective for the treatment of bullous variant of CSC in the short term and internal drainage could lead to anatomical and functional improvement [13, 14]. In fact, the treatment for bullous retinal detachment has not been well established.…”
Section: Discussionmentioning
confidence: 99%